Metode Cooperative Learning Model Student Team Achievement Division (STAD) Sebagai Alternatif dalam Menciptakan Pembelajaran Aktif dan Menyenangkan Pada Mata Pelajaran PAI - Nur Wijayanti (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2016)
AbstractOne of the causes of students being unable to learn PAI materials actively, creatively, eagerly, cheerfully, and fun for a good achievement is that they have not been able to learn cooperatively. Each Student should be able to cooperate in their learning activities through exchange of ideas and experiences. They also need to be given the opportunity of all efforts in group learning activities to improve the ability that has been owned and improve students' skills in aspects of knowledge (cognitive), attitude, and skills (psychomotor). And cooperative learning STAD model becomes an alternative method to realize the needs of students in learning to think, solve problems, and integrate knowledge and skills.Keywords : cooperative learning, student team achievement division